Complement-Dependent Activity of CD20-Specific IgG Correlates With Bivalent Antigen Binding and C1q Binding Strength - Bondza, Sina; Marosan, Anita; Kara, Sibel; Lösing, Josephine; Peipp, Matthias; Nimmerjahn, Falk; Buijs, Jos; Lux, Anja (Frontiers in Immunology, 2021)
Monoclonal antibodies directed against the CD20 surface antigen on B cells are widely used in the therapy of B cell malignancies. Upon administration, the antibodies bind to CD20 expressing B cells and induce their depletion via cell- and complement-dependent cytotoxicity or by induction of direct cell killing. The three antibodies currently most often used in the clinics are Rituximab (RTX), Ofatumumab (OFA) and Obinutuzumab (OBI). Even though these antibodies are all of the human IgG1 subclass, they have previously been described to vary considerably in the effector functions involved in therapeutic B cell depletion, especially in regards to complement activation. Whereas OFA is known to strongly induce complement-dependent cytotoxicity, OBI is described to lack complement activation. In contrast, the role of complement in RTX-induced B cell depletion is still under debate. Some of this dissent might come from the use of different in vitro systems used for characterization of antibody effector functions. We therefore set out to systematically compare antibody and C1q binding and complement-activation by RTX, OFA and OBI on human B cell lines that differ in expression levels of CD20 and complement-regulatory proteins as well as human primary B cells. Applying real-time interaction analysis, we show that the overall strength of C1q binding to live target cells coated with antibodies positively correlated with the degree of bivalent binding for the antibodies to CD20. Kinetic analysis revealed that C1q exhibits two binding modes with distinct affinities and binding stabilities, with exact numbers varying both between antibodies and cell lines. Furthermore, the utilized target cell had a pronounced impact on complement-dependent cell killing of RTX and OBI, whereas the superior complement activation by OFA was independent of the target B cells. All three antibodies were able to initiate deposition of C3b on the B cell surface, although to varying extent. This suggests that complement activation occurs but might not necessarily lead to induction of complement-dependent cytotoxicity. This activation could, however, initiate complement-dependent phagocytosis as an alternative mechanism of therapeutic B cell depletion.